2017
DOI: 10.5152/eurasianjmed.2016.150013
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Characteristics of Thalassemia Major Patients

Abstract: Objective: Thalassemias major are the most common autosomal recessive disorders; they are characterized by anomalies in the synthesis of the beta chains of hemoglobin and are often associated with varying degrees of craniofacial anomalies. The purpose of this study was to evaluate the craniofacial dimensions of b-thalassemia patients and to identify differences by comparing them to those of a control group. Materials and Methods:The study comprised 43 thalassemia major patients and 26 age-and sexmatched health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 14 publications
4
26
2
Order By: Relevance
“…Initial observational studies of the craniofacial complex of thalassaemia patients have shown that they are more prone to a Class II skeletal pattern (increased facial convexity with the mandible positioned posteriorly www.nature.com/scientificreports/ at the sagittal level in relation to the maxilla), without being able to define the exact structural differences from the normal population that could support their findings 10,11 . Further observational anthropometric studies are available 14,[32][33][34][35][36] , while 6 more studies [15][16][17][37][38][39] and one systematic review 40 could be found in the literature. These studies used conventional cephalometrics to compare beta thalassaemia patients with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Initial observational studies of the craniofacial complex of thalassaemia patients have shown that they are more prone to a Class II skeletal pattern (increased facial convexity with the mandible positioned posteriorly www.nature.com/scientificreports/ at the sagittal level in relation to the maxilla), without being able to define the exact structural differences from the normal population that could support their findings 10,11 . Further observational anthropometric studies are available 14,[32][33][34][35][36] , while 6 more studies [15][16][17][37][38][39] and one systematic review 40 could be found in the literature. These studies used conventional cephalometrics to compare beta thalassaemia patients with controls.…”
Section: Discussionmentioning
confidence: 99%
“…6 This finding of present study also commensurate with the study of Karakas S et al who concluded significantly larger total upper lip height (sn-sto) in their study. 1…”
Section: Discussionmentioning
confidence: 99%
“…Thalassemia are group of single gene inherited hematological disorders caused by deficiencies in the synthesis of hemoglobin chains that cause haemolytic anemia . [1] . ß-thalassemia major is the most severe form leading to severe anemia in infancy or childhood and used to be life threatening in absence of regular red cell transfusions [2] .…”
Section: Introductionmentioning
confidence: 99%